The aromatic profile of wine distillates from Ugni blanc grape musts is influenced by the nitrogen nutrition (organic vs. inorganic) of Saccharomyces cerevisiae. (May 2023) - Guittin, Charlie; Maçna, Faïza; Barreau, Adeline; Poitou, Xavier; Sablayrolles, Jean-Marie; Mouret, Jean-Roch; Farines, Vincent
Abstract: Although the impact of nitrogen nutrition on the production of fermentative aromas in oenological fermentation is well known today, one may wonder whether the effects studied are the same when winemaking takes place at high turbidities, specifically for the production of wines intended for cognac distillation. To that effect, a fermentation robot was used to analyze 30 different fermentation conditions at two turbidity levels with several factors tested: (i) initial addition of nitrogen either organic (with a mixture of amino acids - MixAA) or inorganic with di-ammonium phosphate (DAP) at different concentrations, (ii) variation of the ratio of inorganic/organic nitrogen (MixAA and DAP) and (iii) addition of different single amino acids (alanine, arginine, aspartic acid and glutamic acid). A metabolomic analysis was carried out on all resulting wines to have a global vision of the impact of nitrogen on more than sixty aromatic molecules of various families. Then, at the end of the alcoholic fermentation, the wines were micro-distilled. A first interesting observation was that the aroma profiles of both wines and distillates were close, indicating that the concentration factor is rather similar for the different aromas studied. Secondly, the fermentation kinetics and aroma results have shown that the nitrogen concentration effect prevailed over the nature of nitrogen. Although the lipid concentration was in excess, an interaction between the assimilable nitrogen and lipid contents was still observed in wines or in micro-distillates. Alanine is involved in the synthesis of acetaldehyde, isobutanol, isoamyl alcohol and isoamyl acetate. Finally, it was demonstrated that modifying the ratio of assimilable nitrogen in musts is not an interesting technological response to improve the aromatic profile of wines and brandies. Indeed, unbalance the physiological ratio of the must by adding a single source of assimilable nitrogen (organic or inorganic) has been shown to deregulate the synthesis of most of the fermentation aromas produced by the yeast. Wine metabolomic analysis confirmed the results that had been observed in micro-distillates but also in the other aromatic families, especially on terpenes. The contribution of solid particles, but also yeast biosynthesis (via sterol management in must) to wine terpenes is discussed. Indeed, the synthesis of terpenes in this oenological context seems to be favored, especially since the concentration of assimilable nitrogen (in addition to the lipid content) favor their accumulation in the medium. A non-negligible vintage effect on the terpene profile was also demonstrated with variations in their distribution depending on the years. Thus, the present study focuses on the metabolism of wine yeasts under different environmental conditions (nitrogen and lipid content) and on the impact of distillation on the fate of flavor compounds. The results highlight once again the complexity of metabolic fluxes and of the impact of nitrogen source (nature and amount) and of lipids. Furthermore, this study demonstrates that beyond the varietal origin of terpenes, the part resulting from the de novo synthesis by the yeast during the fermentation cannot be neglected in the context of cognac winemaking with high levels of turbidity. Highlights: The nature of the nitrogen in the must and the variation of the mineral/organic nitrogen ratio were studied. Study on a natural must at high turbidities: 500 and 1500 NTU. Metabolomic analysis of wine aromas, including varietal aromas. Micro-distillation of wine and aroma analysis on distillate. Aroma conservation between wine and distillate.